Teachers' socio-spatial practice in innovative learning environments - Lai, Chun; Huang, Yvonne Xianhan; Lam, Tungfei (Cambridge journal of education, 2020)
Understanding the relationship between innovative learning spaces and teachers' pedagogical and social practices is essential given the increasing investment in innovative learning spaces worldwide. This study examined the socio-spatial practices of a group of teachers at a secondary school in an innovative learning space. Interview responses from 21 teachers revealed that space and social practices co-became through the interplay of the school culture, the physical, social and curriculum structures, and individual teachers' sense-making of the practice. The study found that the cultural and structural systems drove the initial becoming of social practices, and that the individual systems shaped the diversified nature of the becoming. The findings suggest the importance of supporting teachers' sense-making in terms of conceptions of subject teaching, professional identity, the affordances and constraints of the space and confidence in and capacity of constructing and managing effective learning experience in the space, when effecting educational changes with space.